Design and evaluation of turbines for use in OWC power plants - Herring, S. (Cranfield University, 2007)
The thesis describes the work carried in developing a process for designing an impulse turbine for use in an Oscillating Water Column power plant, and the design, commissioning, and use of a unique laboratory-based test facility for evaluating such turbines. The test facility is unique both in enabling a wide range of oscillatory flow conditions to be simulated, and in being of a sufficiently large scale to give confidence in the performance results obtained. The use of the test facility to gather performance data for a datum turbine configuration is described and results presented which show good agreement between the predicted and measured performance. In addition to this, the development of a novel turbine configuration which is expected to lead to a step-change in the performance of such devices, and a proof-of-concept turbine configuration which is to be tested in the facility are described. The work has led to a number of conclusions and recommendations for further improvements to both the turbine design and the test facility.